Language Variations in the Tetralogy Supernova: Kesatria, Putri dan Bintang Jatuh by Dewi Lestari (Study on Language and Gender) - Nissa Puspitaning Adni (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2022)
The paper presents the results of research on the relationship between language and gender, in the perspective of social phenomena, on which the language variation is not related to the built phonology, grammar and lexicon, but more to do with semantics or meaning of the language contained in the language. Lakoff (1975) states that there exist variations in the use of language which is based on a specific gender. It is said that, the language used by men tend to be right on target or not long-winded, blunt, flat intonation, and a purely cognitive or does not show colours over their emotions. Meanwhile, women's language is the opposite. This research applies the qualitative by taking its primary data from first supernova tetralogy novel, with the title Kesatria, Putri, dan Bintang Jatuh